Comportamento das séries hidrológicas e mudanças no uso e cobertura do solo na bacia hidrográfica do rio de Contas, Bahia - Teixeira, Laize Eloy (2023)
The news circulating around the world shows that countries, even developed ones, are not able to contain floods, floods, and fires. In Brazil, rains have caused tragedies in some regions, such as Bahia, where several cities are being affected, while droughts have stood out in other regions. From this perspective, this work aims to evaluate the impact of precipitation and land use and occupation on the flows of the Contas river basin, which is entirely located in the state of Bahia. For this purpose, MapBiomas was used, a technology aimed at annually mapping land cover and use and monitoring changes in the territory in order to identify the behavior of the following classes: agricultural, non-vegetated, water bodies, and forest in the basin. Therefore, the hydrological behavior was evaluated through annual precipitation, maximum monthly annual precipitation, precipitation in the wettest and driest quarters. At the hydrometric station, historical series of annual average flow, minimum flow of fifteen days, maximum annual flow, and permanence curve were analyzed. To achieve the results, the runoff coefficient and evapotranspiration were calculated. Additionally, for the analysis of trend in the hydrological series, the Mann-Kendall and Pettitt tests were used. Furthermore, consumptive hydrological demands were examined according to data collected through the Institute of the Environment and Water Resources - INEMA, and correlations were performed. By analyzing the temporal evolution of land cover and use, the behavior in flow was observed in order to develop some considerations about the studied phenomenon. Thus, it is inferred that, based on these evaluations, it was possible to recognize some singularities in the basin area, such as: land use and cover mapping that did not have a significant alteration, forest cover had a small increase in the studied period; annual rainfall remains stationary, dry quarter rainfall has a significant decrease, and wet quarter rainfall remains stationary. This situation may lead to an increase in the request for permits, since surface water withdrawals cannot be met during the dry quarter. There was a trend of decrease in Qmean, which may be due to the significant decrease in Q15, and the decrease in flow was not enough to cause a relevant reduction in the runoff coefficient. The minimum flow reached zero in 1987, thus, the river became intermittent. Over the years, there has been an increase in the water demand of the basin, regarding the existing surface water withdrawals, among which human consumption and public water supply stand out. The annual average flow granted in the area exceeds the value of Q90. However, in the short term, if the behavior of the permits continues as it is, the river may dry up, while precipitation may continue to decrease.